Pipeline Embolization Device for the Treatment of Ruptured Intracerebral Aneurysms: A Multicenter Retrospective Study - Zhong, Weiying; Kuang, Hong; Zhang, Ping; Yang, Xinjian; Luo, Bin; Maimaitili, Aisha; Zhao, Yuanli; Song, Donglei; Guan, Sheng; Zhang, Hongqi; Wang, Yang; Wang, Donghai; et al. (Frontiers in Neurology, 2021)
Background and Purpose: The utilization of flow diversion for ruptured intracerebral aneurysms (IAs) is still limited. We aimed to demonstrate our multicenter experience using the pipeline embolization device (PED) for ruptured IAs that were difficult to treat by clipping and coiling. Methods: Thirty-eight patients with ruptured IAs who underwent PED treatment from 2015 to 2020 were retrospectively reviewed. Factors associated with procedure-related stroke (ischemic and hemorrhagic) and clinical and angiography outcomes were analyzed. Results: There were 14 (36.8%) saccular IAs, 12 (31.6%) blister-like IAs, and 12 (31.6%) dissecting IAs. Perforator involvement was noted in 10 (26.3%) IAs. Early PED placement ( ≤ 15 days) and adjunctive coiling treatment were performed in 27 (71.1%) and 22 (57.9%) cases, respectively. The overall rate of stroke-related complications was 31.6% (12/38) (including rates of 10.5% for procedure-related hemorrhagic complications and 15.8% for procedure-related infarction). The mortality rate was 13.2% (5/38), and 84.2% of patients (32/38) had favorable outcomes. Thirty-two (84.2%) patients underwent follow-up angiographic evaluations; of these, 84.4% (27 patients) had complete occlusion and 15.6% had incomplete obliteration. Multivariate analysis revealed that early PED placement was not associated with a high risk of procedure-related stroke or an unfavorable outcome. Adjunctive coiling exhibited an association with procedure-related stroke (p = 0.073). Procedure-related hemorrhagic complications were significantly associated with an unfavorable outcome (p = 0.003). Immediate contrast stasis in the venous phase was associated with complete occlusion during follow-up (p = 0.050). Conclusion: The PED is a feasible and effective treatment to prevent rebleeding and achieve aneurysm occlusion, but it is associated with a substantial risk of periprocedural hemorrhage and ischemic complications in acute ruptured IAs. Therefore, the PED should be used selectively for acutely ruptured IAs. Additionally, adjunctive coiling might increase procedure-related stroke; however, it may reduce aneurysm rebleeding in acutely ruptured IAs. Patients with immediate contrast stasis in the venous phase were more likely to achieve total occlusion. A prospective study with a larger sample size should be performed to verify our results.